Comparison of Transient Elastography and Liver Biopsy in Assessing Fibrosis in Patients with Nonalcoholic Fatty Liver Disease - Gaurav Bachhav; Lokesh Locheruvapalli Venkateshappa; Balekuduru Avinash; Manjunath Patil; Satyaprakash Bonthala Subbara; Sindhuvalada Karnam Ravikiran (Journal of Renal and Hepatic Disorders)
Nonalcoholic fatty liver disease (NAFLD) is a common cause of chronic liver disease. Ultrasound-based transient elastography (TE) or TE of the liver is a noninvasive tool for effectively evaluating liver stiffness and fibrosis. The study aimed to compare the accuracy of TE as assessed by Fibroscan with liver biopsy in staging fibrosis in patients with NAFLD. Consecutive NAFLD patients (N = 72) were prospectively enrolled. TE evaluation was performed with Fibroscan and compared with liver biopsy, which is a reference standard. Fibrosis was staged according to the METAVIR scoring system (Meta-analysis of Histological Data in Viral Hepatitis). TE scores and biopsy-related fibrosis stages were correlated. Diagnostic accuracy (sensitivity, specificity, positive and negative predictive values) of TE was evaluated. Data were analyzed using software R v3.6.3. Liver biopsy showed that 36.11% of patients did not exhibit fibrosis, whereas 25, 16.67, 15.28, and 6.94% of patients had stage F1 (por-tal/mild fibrosis), F2 (periportal/moderate fibrosis), F3 (bridging/severe fibrosis), and F4 (cirrhosis/advanced fibrosis), respectively. TE showed that 50% of patients had cirrhosis, whereas 20.83,15.28, and 13.86% of patients had mild, moderate, and severe fibrosis, respectively. TE had 71% accuracy, 89% sensitivity, and 38% specificity in diagnosing the severity of fibrosis. Hence, it can be implemented as a noninvasive alternative diagnostic tool for understanding the severity of fibrosis in patients with NAFLD. Moreover, it can also be used for quick early diagnosis of NAFLD, reliable staging of fibrosis, and understanding the need for liver transplantation in patients with NAFLD.